(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: The emphasis on the use of surfactants in enhancing drug release from fatty suppository bases has always been on the concentration and type of surfactants. However, the Hydrophile-Lipophile Balance (HLB) of the surfactants added, the concentrations and the type of suppository base used have significant effects. Objective: The study aimed to evaluate the effect of HLB of incorporated mixed surfactants, the concentration, and the type of base used on the physical and release properties of Ibuprofen suppository formulations. Methodology: Ibuprofen suppositories (200mg) were prepared using Witepsol® H15, Suppocire® CM, Witepsol® W35, Witepsol® E85 semi-synthetic bases. Mixed surfactants (Span® 80 and Tween® 80) were added at 4 %w/w in varied ratios to give HLB values of 4.3 to 15.0, and at 2 and 6% w/w at optimum HLB. The suppositories’ physical properties and release profiles were evaluated using established procedures. Results: The release followed Witepsol® W35>Witepsol® H15>Suppocire® CM>Witepsol® E85. Release from Suppocire® CM and Witepsol® E85 was favored at lipophilic HLB while release from Witepsol® W35 and Witepsol® H15 was favored at hydrophilic HLB. There was a general increase in the release of Ibuprofen with the increase in the concentration of mixed surfactants at the optimum HLBs. The release kinetics were majorly fitted for Higuchi’s kinetic model and followed Fickian and Non-Fickian (anomalous) drug transport mechanisms depending on the HLB of the mixed surfactants. Conclusions: The HLB, concentration of mixed surfactants, and the type of base greatly influenced the variation in the release profile of the Ibuprofen suppository.